MUSICAL PRACTICES AND MUSICAL SUSTAINABILITY IN THE KÖÇEK TRADITION - İlhan, Serap Yağmur (Tolga Karaca, 2025)
This study explores the musical dimensions of the köçeklik tradition, a performative cultural practice that has continued from the Ottoman period to the present day. It aims to examine the function and sustainability of music within this tradition by focusing on key elements such as the types and numbers of instruments used, the influence of music technology, key considerations in instrumental performance, acquisition of musical skills, commonly preferred pieces, performance venues, public perceptions, and challenges faced in musical execution. Using a qualitative case study design, data were collected through semi-structured interviews with 15 participants, including köçeks and instrumentalists. To strengthen the findings, selected musical works mentioned in the interviews were analyzed using document analysis methods. The study reveals that köçeklik encompasses more than local musical practices; it is sustained through a complex and multidimensional structure. Notably, the minimal integration of technology is seen as beneficial to the tradition’s continuity. Additionally, the tradition demands high attention to musical detail, indicating its performative richness. This research contributes to a deeper understanding of the köçeklik tradition as a comprehensive musical and cultural phenomenon. © 2025, Tolga Karaca. All rights reserved.
KÖÇEKLİK GELENEĞİNDE MÜZİK PRATİKLERİ VE MÜZİKAL SÜRDÜRÜLEBİLİRLİK
Keywords: Köçek tradition; music and dance; musical practices; sustainability; traditional performance